Electronic Licensing as a Solution to Licensing Process Problems in Siak and Karo District - Adi Suhendra (International Journal of Regional Innovation, 2021)
This study discusses public service innovations related to public or business licensing. Where, in this study, it will be discussed related to the problems or obstacles faced by the district in terms of licensing, as well as solutions that are carried out by creating innovations. This study discusses public service innovations related to public or business licensing. Where, in this study, it will be discussed related to the problems or obstacles faced by the district in terms of licensing, as well as solutions that are carried out by creating innovations.This study uses a qualitative method.The population in this study is the area that has made innovations in order to overcome the problems that hinder the licensing process in the district community. While the research subjects are Siak Regency with the innovation of Fast Licensing with SINSE (Notification Information System and Electronic Certificate), and Karo Regency with the name of Electronic Licensing Service innovation (E-Perizinan Si-Cantik).This research shows that the local government with the support of the community has succeeded in finding solutions related to the problems that hinder community licensing. With the innovation in the licensing sector, it can improve services to the community, facilitate the search for licensing information, shorten time, and create effective and efficient licensing procedures.